KEMUNCULAN LITERASI SAINS PADA MODUL PRAKTIKUM BERBASIS KONTEN, PROSES DAN KONTEK DI SMP NEGERI 1 KOTA LANGSA - Nursamsu Nursamsu; Rizky Nafaida; Dona Mustika (Universitas Islam Negeri Ar-Raniry, 2019)
In the 21st century the importance of scientific literacy learning is a necessity for individuals who face the challenges of the development of rapid scientific progress. Since that, science literacy learning is a learning concept based on content, processes and contexts. The basis of this research is about practicum modules that apply the concept of scientific literacy. The purpose of this study is to find out the indicators of the scientific literacy in the practicum module in Junior High School 1 in Langsa City. The method in this study is descriptive quantitative. The results obtained in this study are: (1) the content aspect of the scientific literacy in practicum module is 39%, (2) the process aspect of the scientific literacy is 52% which stated that the scientific literacy sometimes appears in the practicum module; (3) the context aspect is 40% which stated that the scientific literacy sometimes appears in the practicum module. The result is that practicum module can be stated sufficiently related to scientific literacy.